The Institution of Full Powers in the Process of Concluding International Agreements - Bąkowski, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
This paper addresses issues related to the institution of full powers in the process of concluding international agreements. The author makes an analysis of the historical evolution of the institution of full powers and discusses the essential elements of the full powers instrument with regard to the representation of the state and international organizations, taking into account current international law regulations. In this regard, the author also refers to international practice and, based on a review of the scholarly literature, attempts to classify full powers.